Indoor and outdoor characterisation of organic and inorganic compounds in city centre and suburban elementary schools of Aveiro, Portugal - Pegas, P. N. (2019)
Pollutants inside school buildings may affect children's health and influence learning performance and attendance. This study investigated pollutant concentrations inside and outside school buildings at different locations (city centre and suburban) in Aveiro, Portugal, between April and June 2010. The aim was to evaluate simultaneously comfort parameters (temperature, relative humidity, CO2 and CO) and indoor and outdoor concentrations of VOCs, NO2, PM10 and bioaerosols. PM10 samples were analysed and characterised, for the first time, for the water soluble inorganic ions (WSII), organic carbon (OC), elemental carbon (EC), carbonates, and detailed organic speciation. The CO2 and bioaerosol levels were higher than the acceptable maximum values to the occupants' comfort. Concentrations of the traffic tracer NO2 were higher outdoors. The daily indoor PM10 levels were always higher than those outdoors, except on weekends, suggesting that the physical activity of pupils and class works highly contributed to the emission and resuspension of particles. Almost all identified VOCs showed I/O ratios higher than one, which denotes an important contribution from indoor sources at both schools. The suburban school was more exposed to industrial emissions than the institution located in the city centre. Especially at the city centre, infiltration of outdoor particulates leads to contamination of school indoor environment with vehicle emissions and biomass burning smoke likely coming from biofuel use in nearby restaurants and bakeries.